Faire construire les logements sociaux par le secteur privé. Les leviers insoupçonnés de la Région bruxelloise en matière de TVA - Nicolas Bernard; Edoardo Traversa (Brussels Studies)
As we know, there is a dramatic lack of social housing in the Brussels Region. While the VAT system undoubtedly benefits the public production of social housing (by granting a reduced rate of 6 %), it does not help private operators or associations which also have the vocation to provide housing at a modest price (without going through a social housing agency). Moreover, this differentiated VAT system violates two fundamental legal principles: equal treatment and tax neutrality (according to which two similar operations in terms of their results must be subject to a similar tax regime). It is therefore time to change this tax measure. But what can the Brussels Region do when this tax falls within the remit of the federal government? There are at least two things it can do: include the private construction of social housing in the category of “social housing corporation” (which already benefits from the reduced VAT rate) or, failing that, grant a subsidy to the former activity in order to compensate for the difference between the standard VAT rate (which will be applied) and the reduced rate. All of this, of course, would be subject to social conditions, such as selling a certain proportion of the housing produced to a social housing corporation and making the sale (or rental) of the remainder subject to certain social conditions. By involving the private sector in this way, it could be possible to shorten the very long waiting list for social housing.